Risk factors for total laryngectomy associated proximal esophageal stricture formation in head and neck cancer patients - Schulz, Dominik; Koob, Isabelle; Pickhard, Anja; Schmid, Roland M.; Abdelhafez, Mohamed (Zeitschrift für Gastroenterologie, 2023)
Background Development of esophageal strictures is common after the total laryngectomy of head and neck cancer patients. While endoscopic techniques like dilatation by balloon or Salvary bougies are well established, risk factors and pathophysiology for development of refractory strictures are less well understood.Objective To evaluate risk factors associated with occurrence and recurrence of total-laryngectomy-associated esophageal strictures in head and neck cancer patients.Methods We analyzed retrospectively a cohort of 170 head and neck squamous cell carcinoma patients, who underwent total laryngectomy between 2007 and 2017. The outcome measure was laryngectomy-associated proximal esophageal stricture needing an endoscopic dilatation by using a balloon or Savary dilators.Results Of the 170 patients in the cohort, 32 (18.8%) developed strictures. Mean time between surgery and first endoscopic intervention was 24.4 months. Significant predictive factors were age ≥ 65 (p=0.017), nodal status N> 1 (p=0.003), continued alcohol abuse after surgery (p=0.005) and diabetes mellitus (p=0.005). In a subgroup, 17 of 32 patients developed refractory strictures and needed more than three dilatations to relieve dysphagia. Postoperative mean (p=0.016) and maximum (p=0.015) C-reactive protein (CRP) were predictive for refractory strictures.Conclusion Symptomatic strictures occurred in 18.8% of the cases. Age, nodal status N>1, continued alcohol abuse and diabetes mellitus were predictive factors. For refractory stenosis (>3 dilatations needed) mean and maximum postoperative CRP were predictive. This may indicate that systemic inflammatory response post-surgery is involved in the stricture formation process.
Keywords: HNSCC; esophageal stricture; risk factors; dilatation